Determinants of Leadership and Organizational Culture in Implementing Business Strategies - Zainal Ilmi; Robiansyah Robiansyah; Michael Hadjaat; Saida Zainurossalamia ZA; Dio Caisar Darma (SEISENSE Business Review)
Leadership and organizational culture are essential factors in the sustainability of a business. The two things' strategy becomes a concept that is often used as a foundation by various companies in running their activities. This article aims to discuss the role of leadership and organizational culture in implementing business strategy. Societal, cultural norms influence leader attributes and behaviors. Leader attributes and actions can be affected by the organization's corporate environment, size, and technology. Leader attributes and behaviors can determine the organizational form and organizational culture, and vice versa.